Laser machining of transparent brittle materials: from machining strategies to applications - Xie Xiaozhu (Institue of Optics and Electronics, Chinese Academy of Sciences, 2019)
Transparent brittle materials such as glass and sapphire are widely concerned and applied in consumer electronics, optoelectronic devices, etc. due to their excellent physical and chemical stability and good transparency. Growing research attention has been paid to developing novel methods for high-precision and high-quality machining of transparent brittle materials in the past few decades. Among the various techniques, laser machining has been proved to be an effective and flexible way to process all kinds of transparent brittle materials. In this review, a series of laser machining methods, e.g. laser full cutting, laser scribing, laser stealth dicing, laser filament, laser induced backside dry etching (LIBDE), and laser induced backside wet etching (LIBWE) are summarized. Additionally, applications of these techniques in micromachining, drilling and cutting, and patterning are introduced in detail. Current challenges and future prospects in this field are also discussed.